PREFERENSI KONSUMEN TERHADAP MINUMAN SUSU FERMENTASI DI TIGA MALL KOTA PEKANBARU - Kasmadi Kasmadi; Irdha Mirdhayati; Elfi Rahmadani (State Islamic University of Sultan Syarif Kasim Riau, 2011)
This research was conducted to know consumen preferences to comercial fermented milk in order to: frequency ofconsumption, form of consumption, type of fermented milk, place to take the product and reason consumption. Total samplewas used 100 respondences in three Malls Pekanbaru City. Result showed that highest frequency of comsumption wasweekly, form of comsumption was ready to drink, type of product yakult, place to take the product was supermaket and thereason to consumption was benefit to their healthy.